2001
DOI: 10.7901/2169-3358-2001-1-649
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the Erika Oil Spills

Abstract: On December 12, 1999, the Erika tanker broke in two sections at about 30 miles from the Brittany coast in the Bay of Biscay, France. The two parts of the wreck sank a few hours after the break. Some 15,000 tons of heavy fuel were released into the manne environment. It is the most serious discharge that has occurred in France since 1980 (Tanio, 6,000 tons). The nature of the incident, the kind and quantity of oil spilled, and the prevailing weather conditions posed considerable response problems. The spilled o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 3 publications
(1 reference statement)
1
15
0
Order By: Relevance
“…Contaminant contours depict the time and length scales of the spill and it has been shown that large areas can be affected in a few hours. Random-walk method proved to be a successful method in many applications (Cekirge and Palmer, 2001;Daniel et al, 1998;Daniel et al, 2001). Our study shows that it provides reasonable answers in modeling the diffusion phenomenon in the Strait of Istanbul.…”
Section: Discussionsupporting
confidence: 55%
“…Contaminant contours depict the time and length scales of the spill and it has been shown that large areas can be affected in a few hours. Random-walk method proved to be a successful method in many applications (Cekirge and Palmer, 2001;Daniel et al, 1998;Daniel et al, 2001). Our study shows that it provides reasonable answers in modeling the diffusion phenomenon in the Strait of Istanbul.…”
Section: Discussionsupporting
confidence: 55%
“…New developments, exercises and training are jointly conducted with CEDRE (Centre de documentation de recherche et d'expĂ©rimentations sur les pollutions accidentelles des eaux). MOTHY correctly predicted the drift of the oil during Erika crisis (December 1999) in the Bay of Biscay (Daniel, 2001). …”
Section: -Introductionmentioning
confidence: 83%
“…Contaminant contours depict the time and length scales of the spill and it has been shown that large areas can be affected in less than a week. Random-walk method proved to be a successful method in many applications (Cekirge and Palmer, 2001;Daniel et al, 2001;Daniel et al, 2001) and it performed well in modeling the diffusion phenomenon in the Sea of Marmara.…”
Section: Discussionmentioning
confidence: 99%